Methods of increasing cultural competence in nurses working in clinical practice: A scoping review of literature 2011–2021 - Červený, Martin; Kratochvílová, Inka; Hellerová, Věra; Tóthová, Valérie (Frontiers in Psychology, 2022)
Aim Training for the development of cultural competence is often not part of the professional training of nurses within the European Economic Area. Demographic changes in society and the cultural diversity of patients require nurses and other medical staff to provide the highest quality healthcare to patients from different cultural backgrounds. Therefore, nurses must acquire the necessary cultural knowledge, skills, and attitudes as part of their training and professional development to provide culturally competent care to achieve this objective. Objective This review aims to summarize existing methods of developing cultural competence in nurses working in clinical practice. Design A scoping review of the literature. Method The following databases were used: PubMed, ScienceDirect, ERIH Plus, and Web of Science using keywords; study dates were from 2011 to 2021. Results The analysis included six studies that met the selection criteria. The studies were categorized as face-to-face, simulations, and online education learning methods. Conclusion Educational training for cultural competence is necessary for today’s nursing. The training content should include real examples from practice, additional time for self-study using modules, and an assessment of personal attitudes toward cultural differences.